Development of a moisture buffer value model (MBM) for indoor moisture prediction. (5th May 2020) - Zu, Kan; Qin, Menghao; Rode, Carsten; Libralato, Michele
Highlights: Moisture buffer values (MBVs) under different boundary conditions are proposed. Time-average MBV is introduced to calculate the indoor moisture conditions. A new moisture buffer value model (MBM) is developed for building simulation. The MBM model can provide a fast and accurate indoor moisture prediction. Abstract: Hygroscopic materials could be used to passively regulate indoor moisture fluctuations, and thus reduce building energy consumption. It is essential to accurately calculate the moisture buffering effect in building energy simulations. However, in many building simulation tools, moisture buffering has been neglected. In those building tools that include moisture model, moisture buffering either has been estimated by very simple approximations or has been calculated by complex coupled heat-air-moisture transfer models that require orders of magnitude more computing time than simple energy prediction. Here, we have developed a new moisture prediction model with fast solution time and reasonable accuracy based on the moisture buffer value (MBV) theory. The MBV was originally designed to evaluate the moisture buffering capacity of building materials. Little research has been carried out to directly use MBV for building energy simulations. This paper first investigates MBVs under different boundary conditions. Secondly, a time-average MBV has been proposed, and its parameters can be obtained from the practical MBV test. Finally, comparison tests between the new moisture buffer value model (MBM) and other moisture prediction models have been carried out. The results indicate that the MBM can provide a fast and reasonably accurate prediction for indoor moisture variation.